Design of design: Learning dynamics in design degree - Delgado, M. J.; Duarte de Almeida, I.; Montagna, G.; Silva, J. V.-B. da. (Advances in Intelligent Systems and Computing, 2019)
Though different College’s curriculums in Design point to different objectives, there may be low awareness about different stakeholder’s real needs in issues like design relevance, planning, production, marketing, selling and recycling of designed products. The curricular programs include the approximation of the Design students (DS) to the job market with the purpose of professional success. However, the labor-market-approach focus must also include the challenge of entrepreneurship, based on the transformation of DS projects into competitive products. Having in mind the relevance of the analysis of DS entrepreneurship predisposition, and the need to stimulate this target to transform the DS skills in order to develop business, this paper intends to: (1) profile the DS regarding their entrepreneurial competencies and capabilities, and (2) to know how to tailor Design curriculum and proposing tools (Canvas) in order to develop/align new DS skills for development/implementation of business projects.